The Role of Teacher Talk in Enhancing Communicative Competence in EFL Classrooms in Indonesia - Goestina Goestina; Sugirin Sugirin (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: This research investigates the role of teacher talk in enhancing students' communicative competence within classroom practices at SMA Muhammadiyah 1 Unismuh Makassar. Using a qualitative research design, the study was carried out at SMA Muhammadiyah 1 Unismuh Makassar. Data collection involved audio recordings of teacher-student interactions during classroom observations, supported by interviews and document analysis. By employing this triangulated approach, the study ensured the reliability of its findings by corroborating data from multiple sources. The focus was on English as a Foreign Language (EFL) classrooms, offering valuable insights into how teacher talk contributes to fostering an interactive and supportive learning atmosphere. The findings indicate that teacher talk plays a crucial role in guiding and motivating students while facilitating active participation in classroom activities. Teachers employed a range of strategies, including acknowledging students' emotions, providing praise, integrating students' ideas, delivering information, correcting errors, asking questions, giving instructions, and encouraging engagement. Teacher talk was categorized into two key functions: instructional and managerial. Instructional talk primarily involved explaining and clarifying learning materials, while managerial talk aimed to maintain classroom order and promote student involvement in activities. The study concludes that well-organized teacher talk significantly supports the development of students' communicative competence. By strategically structuring classroom discourse, teachers help students effectively interact with both learning materials and classroom activities, creating an environment conducive to language acquisition. These findings highlight the importance of reflective practices among EFL teachers to refine their communication strategies and enhance learning outcomes. Keywords: teacher talk, communicative competence, EFL classroom, qualitative research, instructional strategies, classroom management, language acquisition.